2020
DOI: 10.1103/physrevresearch.2.023061
|View full text |Cite
|
Sign up to set email alerts
|

Universal theory of brain waves: From linear loops to nonlinear synchronized spiking and collective brain rhythms

Abstract: An inhomogeneous anisotropic physical model of the brain cortex is presented that predicts the emergence of nonevanescent (weakly damped) wavelike modes propagating in the thin cortex layers transverse to both the mean neural fiber direction and the cortex spatial gradient. Although the amplitude of these modes stays below the typically observed axon spiking potential, the lifetime of these modes may significantly exceed the spiking potential inverse decay constant. Full brain numerical simulations based on pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Hence, similar early works attempted to reduce this irregularity by accounting for the average of multiple signals. Although, this reduced the noise it is now known that even slight irregularities in brain signals still carry out messages [68]. The same was hypothesized for molecular signals in the cellular environment, which has been found that the most important differences were those that took place in infinitesimal ranges.…”
Section: Neuronal Systems As Forms Of Artificial Lifementioning
confidence: 77%
See 1 more Smart Citation
“…Hence, similar early works attempted to reduce this irregularity by accounting for the average of multiple signals. Although, this reduced the noise it is now known that even slight irregularities in brain signals still carry out messages [68]. The same was hypothesized for molecular signals in the cellular environment, which has been found that the most important differences were those that took place in infinitesimal ranges.…”
Section: Neuronal Systems As Forms Of Artificial Lifementioning
confidence: 77%
“…The same was hypothesized for molecular signals in the cellular environment, which has been found that the most important differences were those that took place in infinitesimal ranges. Finally, it is possible that irregularities in neural signaling may actually represent the actual information transmission [67,68]. Overall, neuroscience stated two hypotheses, about the nature of neural information processing.…”
Section: Neuronal Systems As Forms Of Artificial Lifementioning
confidence: 99%
“…This equilibrium solution provides the locus of the bifurcation point at where the nonlinear spiking oscillations occur (as was shown both in 1,2 and in 33 ).…”
mentioning
confidence: 77%
“…evanescent cortical wave (WETCOW) modes 1,2 . The Hamiltonian framework developed for these WETCOW modes in 33 is advantageous in that it explicitly uncovers the reciprocity of the temporal and the spatial dynamics of the evolutionary equations.…”
Section: {T } Kmentioning
confidence: 99%
See 1 more Smart Citation